Kesetimbangan Energi Termal Dan Efisiensi Transient Pengering Aliran Alami Memanfaatkan Kombinasi Dua Energi - Kade Suriadi, I Gusti Agung; Ricki Murti, Made (Jurnal Teknik Industri, 2011)
The energy used as a dryer is usually only a single type of energy. In this case, study is conducted on the natural flowdryer system by using the chimney. This combination of energy utilization of solar energy and biomass that can be used simultaneously or one turns in accordance with the needs or circumstances. It has been tested against a dryer prototype by performing measurements on the temperature of the inlet air and exit on biomass furnace, the temperature of the inlet air and exit on the solar collector, the temperature of inlet air and exit on the drying chamber, the water content of dried material, the temperature of dried material, the surface temperature of inside and outside of wall on drying chamber, and the intensity of solar radiation. Data were collected at an interval of 30 minutes and do the processing of such data. Next made in a graphical form of thermal energy balance and system efficiency versus the time. Results obtained that: the drying time was 7.5 hours. Thermal energy balance versus the time found that the increase of energy losses lead to useful energy reduction system.